Implementation of Guidance and Counselling in Schools by the NCERT’s Trained Teacher Counsellors A Follow-up Study - Dhiwal, Shraddha (INDIAN EDUCATIONAL REVIEW, 2019)
The study explored the changes in the school environment as well as the benefits accrued to students due to the implementation of Guidance and Counselling (G&C) services in the school. Guidance personnel trained from 2009 to 2015 by National Council of Educational Research and Training (NCERT) at New Delhi and its Regional Institutes of Education (RIE) at Ajmer, Bhopal, Bhubaneswar, Mysuru and Shillong, were included in the study. The questionnaires were mailed to 300 Counsellors and 100 Principals. Of these, 146 Teacher Counsellors and 27 Principals returned the filled-in questionnaire (response rate is 49 per cent). Focus Group Discussions were held with 210 secondary level students from Kendriya Vidyalayas, Jawahar Navodaya Vidyalayas and NCERT’s Demonstration Schools. Teacher Counsellors and Principals stated that due to the implementation of G&C services in schools, there is a visible improvement in the school environment. Improvement in academic performance and reduction in drop-out, bullying, violence, aggression and indiscipline among the students were also reported. The subject teachers and parents have developed an understanding of the guidance needs of students, their developmental and behavioural issues and factors responsible for underachievement among the students. Teacher Counsellors suggested that there is a need to develop awareness about G&C, the appointment of regular Teacher Counsellors, providing space for G&C in the timetable, provisioning of funds for conducting G&C activities and separate counsellors for primary and secondary classes for both morning and evening shifts.